KONSTIPASI KRONIS SEBAGAI FAKTOR RISIKO TERJADINYA INFEKSI SALURAN KEMIH PADA ANAK - , dr. Irna Fajri Syahny, Prof. dr. Mohammad Juffrie, Ph.D., Sp.A(K). ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The prevalence of urinary tract infection (UTI) in children is about 2.4-3.5% and the frequency in Sardjito hospital is 3.5%. This condition is still a problem and the prognosis of the patient is depends on the management. UTI was found in 3.7- 42% children with constipation. Rectal dilatation in chronic constipation will press the bladder and obstruct the bladder emptying process that caused by instability of detrussor muscles and discoordination between detrussor contraction and external urethral sphincter relaxation then increased the bladder pressure and residual urine. This process caused the increasing of bacterial growth to UTI. Constipation is the chief complain of about 3% patients who admitted to the pediatrician and 25% of them were solved by pediatric gastroenterologist. Constipation does not become attention for the clinician in UTI pediatric patient management. It is necessary to evaluate the role of chronic constipation in increasing the risk of UTI in children. The aim of the study is to evaluate the role of chronic constipation in increasing the risk of UTI in children and the hypothesis is chronic contipation may increase the risk of UTI in children. The study is conducted in pediatric installation, Sardjito General Hospital, by using case controll study in 2-18 years old children diagnosed as UTI and no history of antibiotic consumption within the last 48 hours before urine culture examination. UTI patient as case group and the patient without UTI as controll group. The patient will exclude from the study if there are history of neurological or anatomical abnormality and using transurethral catheterization. The history of constipation will measure in both case and controll group. Sixty four cases and 64 controll were enrolled in the study. Chronic constipation may 3.7 fold increase the risk for having UTI in children (OR 3.77